EVALUASI PROGRAM SEKOLAH PENGGERAK DI KOTA KEDIRI MENGGUNAKAN MODEL KIRKPATRICK - Sava, Navima Aulya; Kusumawati, Nehha Kusumawati; Hazin, Mufarrihul (Jurnal Manajemen Pendidikan Islam Darussalam, 2024)
This research purpose to provide a comprehensive overview of the successes, challenges, and impacts of the driving school program by evaluating the Driving School program in Kediri City using the Kirkpatrick evaluation model which consists of 4 levels: reaction, learning, behavior, and results. At the reaction level, the education department carries out reflection activities to obtain feedback from the school principal. At the learning level, the education office uses pre-tests and post-tests to measure increases in participants' knowledge, skills and competencies, as well as direct observation by supervisors. At the behavioral level, the education office sees changes in the behavior and competence of school principals and teachers in implementing training results. At the results level, the education department does not yet have specific indicators to measure the long-term impact of the program, but carries out annual reflections to see changes in culture, leadership and involvement of the school community.